Galactooligosaccharide and a combination of yeast and ?-glucan supplements enhance growth and improve intestinal condition in striped catfish Pangasianodon hypophthalmus fed soybean meal diets - Sutriana A.; Hashim R.; Akter M.N.; Nor S.A.M. (Springer Tokyo, 2024)
The effects of galactooligosaccharide (GOS) and a combination of yeast and ?-glucan (Y?G) supplementation of dietary soybean meal (SBM) on the growth and digestive performance of striped catfish Pangasianodon hypophthalmus were evaluated. Four isonitrogenous (30% protein) and isocaloric (19MJ/kg diet) diets were formulated to contain 100% fish meal (FM) protein, 55% FM protein/45% SBM protein, FM-SBM supplemented with 1% GOS, and a combination of 1% yeast and 0.1% ?-glucan, respectively. Each diet was fed for 12weeks to three groups of 30 striped catfish fingerlings (average weight 16.45 0.07g) maintained in circular fiberglass tanks (600l). Growth, feed utilization, and muscle protein composition of fish improved significantly after supplementation with either GOS or Y?G compared to the unsupplemented SBM diet, but were similar to those of fish fed the FM diet. Nutrient digestibility, digestive enzyme activities, villi and microvilli length were significantly increased in fish fed the supplemented SBM diets. The gut microbiota ranking profile showed that supplementing the SBM diet with Y?G and GOS gave a ranking of Verrucomicrobia, Spirochaetes, Bacteriodetes, and Actinobacteria phyla similar to that of the FM diet. Thus, diet containing 45% protein from soybean supplemented with either GOS or Y?G can be recommended to improve the growth and digestive performance of striped catfish. 2018, Japanese Society of Fisheries Science.